The Effect of Family Attention on Learning Motivation of High Class Students in Hukaea Laea State Elementary School - Ahmad Rustam; Dadiwati; Ashari Usman (Arus Jurnal Psikologi dan Pendidikan, 2022)
The research problem formulations are: (1) Is there any effect of family attention on the learning motivation of high-class students at SD Negeri 145 Hukaea Laea, Bombana Regency? The purpose of this study was to determine the effect of family attention on the learning motivation of high-class students at SD Negeri 145 Hukaea Laea, Bombana Regency. The approach used in this research is a quantitative approach. The variables of this research are family attention as the independent variable (Variable X) and learning motivation as the dependent variable (Variable Y). The population of this study were all high-class students and parents at SD Negeri 145 Hukaea Laea, Bombana Regency, amounting to 65 people. The sampling technique used was total sampling so that the sample of this study was 65 students and 65 students' parents. The data analysis of this research used a simple linear regression analysis technique with the help of the SPSS program. The results of this study indicate that: The results of the regression analysis of the X variable against Y, obtained an R value of 0.988 and an R Square value of R Square 0.977, meaning that 97.70% of students' learning motivation in High School SD Negeri 145 Hukaea Laea is determined by family attention. , while 2.23% is determined by other variables. The conclusions of this study are: family attention has a positive and significant effect on the learning motivation of high school students at SD Negeri 145 Hukaea Laea, Bombana Regency. The higher the family's attention, the higher the learning motivation of the students of SD Negeri 145 Hukaea Laea, Bombana Regency, the higher the learning motivation.